2020
DOI: 10.3389/fcell.2020.589761
|View full text |Cite
|
Sign up to set email alerts
|

GFOGER Peptide Modifies the Protein Content of Extracellular Vesicles and Inhibits Vascular Calcification

Abstract: ObjectiveVascular calcification (VC) is an active process during which vascular smooth muscle cells (VSMCs) undergo an osteogenic switch and release extracellular vesicles (EVs). In turn, the EVs serve as calcification foci via interaction with type 1 collagen (COL1). We recently showed that a specific, six-amino-acid repeat (GFOGER) in the sequence of COL1 was involved in the latter’s interaction with integrins expressed on EVs. Our main objective was to test the GFOGER ability to inhibit VC.ApproachWe synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 52 publications
(75 reference statements)
0
8
0
Order By: Relevance
“…Furthermore, an increase in reactive oxygen species (ROS) production is involved in VSMC osteochondrogenic trans-differentiation during the VC process ( Tóth et al, 2020 ; Hu et al, 2021 ). Recent studies have highlighted the role of extracellular vesicles (EVs) in VC ( Hodroge et al, 2017 ; Mansour et al, 2020 ; Yaker et al, 2020 ; Qin et al, 2021 ). These membrane-bound vesicles, secreted by prokaryotic and eukaryotic cells ( Woith et al, 2019 ), can be of various origins, depending on their mode of biogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, an increase in reactive oxygen species (ROS) production is involved in VSMC osteochondrogenic trans-differentiation during the VC process ( Tóth et al, 2020 ; Hu et al, 2021 ). Recent studies have highlighted the role of extracellular vesicles (EVs) in VC ( Hodroge et al, 2017 ; Mansour et al, 2020 ; Yaker et al, 2020 ; Qin et al, 2021 ). These membrane-bound vesicles, secreted by prokaryotic and eukaryotic cells ( Woith et al, 2019 ), can be of various origins, depending on their mode of biogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…These findings were confirmed by Mansour et al, who showed that a synthetic GFOGER peptide could inhibit VC in VSMCs and aortic rings [129]. This effect was accompanied by a change in the EVs' protein content [129].…”
Section: Vsmc-derived Evsmentioning
confidence: 56%
“…Moreover, an oligogalacturonic acid (DP8) was able to block the GFOGER interaction between type I collagen and EVs and thus to reduce VC and VSMC osteogenic switching [128]. These findings were confirmed by Mansour et al, who showed that a synthetic GFOGER peptide could inhibit VC in VSMCs and aortic rings [129]. This effect was accompanied by a change in the EVs' protein content [129].…”
Section: Vsmc-derived Evsmentioning
confidence: 82%
“…Clinically, circulating as well as cell-derived exosomes with a low fetuin-A level play a detrimental role in VC ( 58 , 79 ). While the GFOGER peptide, a six amino-acid repeat present in type 1 collagen, alleviated VC by reducing the content of osteogenic switching–related proteins, such as TANK-binding kinase 1 and casein kinase II, in VSMC-derived EVs ( 80 ). These pieces of evidence remind us that the cargo loaded by exosomes secreted from VSMCs changes dynamically with the progression of VC, which provides potential diagnostic biomarkers and targets for treatment.…”
Section: Exosome-mediated Crosstalk In the Vascular Wall Microenviron...mentioning
confidence: 99%